GIS and environmental monitoring : applications in the marine, atmospheric and geomagnetic fields /: applications in the marine, atmospheric and geomagnetic fields. (2017) - Kolios, Stavros; Vorobev, Andrei V; Vorobeva, Gulnara R; Stylios, Chrysostomos
No abstract available